Effect of In and N incorporation on the properties of lattice-matched GaInNAs/GaAs grown by radio frequency plasma-assisted solid-source molecular beam epitaxy - Loke, Wan Khai (2013)
We present the effect of nitrogen (N) and indium (In) incorporation on the structural and optical properties of with low lattice mismatch to GaAs grown by solid-source molecular beam epitaxy using a radio frequency (rf) nitrogen plasma source. The results show that excessive introduction of nitrogen during the growth of GaInNAs may lead to greater incorporation of interstitial nitrogen and degradation in crystal quality. This effect is more significant in GaInNAs compared to GaNAs. A drastic 6× increase in x-ray diffraction full width at half maximum (XRD-FWHM) was observed in GaInNAs compared to 1.5× increase of the same in GaNAs when reactive nitrogen is introduced into the material. The more significant degradation in GaInNAs quality is believed to be due to greater incorporation of interstitial nitrogen in the presence of indium during growth. By changing the In content and fixing the N incorporation rate, a sample of with relatively low lattice mismatch of −896 ppm (or was grown. Low temperature (4 K) photoluminescence emission at 1518 nm was observed and XRD-FWHM of 118.2 arcsec was measured